The Influence of Static and Dynamic Training Method and Eye-Hand Coordination Training Method toward the Float Serve Accuracy (Journal of Physical Education and Sports, 2019)
This research aims to analyze: the effectivity difference between static target serving training method and dynamic target serving training method toward the float serve accuracy of the extracurricular volleyball students in Public Senior High School 3 Purwokerto. This research uses the experiment method along with factorial 2x2 design. The sampling method used is purposive sampling including ten female athletes and ten male athletes. The data analysis method used is Analysis of Variant (ANOVA) on the significance level (Î±) = 0.05. The variables of this research consist of two manipulative independent variables, namely static target serving training method and dynamic target serving training method, an attributive independent variable namely eye-hand coordination, and a dependent variable namely volleyball float serve accuracy. The results of the research are: the difference between static and dynamic target serving training method toward the float serve accuracy with the significance level of 0.001 and Fvalue = 16.791 > Ftable = 3.47. The difference between high eye-hand coordination ability and low eye-hand coordination ability toward float serve accuracy, with the significance level (Î±) = 0.000 and Fvalue = 140.698 > Ftable = 3.47. The interaction between serving training method (static and dynamic target) and eye-hand coordination (high and low), with the significance level (Î±) = 0.002 and Fvalue = 13.442 > Ftable = 3.47. This research concludes that there is significant influence between static and dynamic target serving training method toward float serve accuracy as well as high and low eye-hand coordination.